Potencjał ewolucyjny metakrytyczności na przykładzie powieści graficznej „Strażnicy” Alana Moore’a i Dave’a Gibbonsa - Wróblewski, Michał (Wydawnictwo Naukowe UAM, 2013)
This article discusses the impact of self-awareness and metacritical tendencies within the texts of popular culture on the development of genres in the politypical chain. The preliminary analysis proposed in the second part of this paper concerns the contemporary comics, which represent the blurring of boundaries between “high” and “low” culture. The author chose Moore’s graphic novel Watchmen as the subject of this brief study. The novel exemplifies evolutionary changes associated with a metacritical attitude introduced in the area of schematic, American superhero graphic stories.
Evolutionary potential of metacriticality in reference to Watchmen – the graphic novel by Alan Moore and Dave Gibbons